Estimating farmers’ willingness to pay for photovoltaic industry to improve agricultural green resources and environment - Li, Jinyang; Khan, Arshad Ahmad; Khan, Sufyan Ullah; Ali, Muhammad Abu Sufyan; Luo, Jianchao (Frontiers in Environmental Science, 2022)
Based on the consideration of the level of the regional radiation effect of the photovoltaic industry, four main regions were selected as case sites in Pingluo County, Ningxia Province, for this research. The study used the double-bound dichotomous CVM model and C-optimal design to revise the bidding value of the payment scheme that reduced the WTP range error. Five independent sub-sample questionnaires, including seven bidding value payment schemes, along with four internal range tests and six external range tests, were designed. The results showed that the comparison of the WTP for the improvement of agricultural resources and the environment among different independent sub-samples in the same region passed the external quantitative scope test, indicating that the questionnaire design, survey implementation, and WTP estimation results of the double-bound dichotomous CVM in this study were reliable. Saturation degree, diminishing marginal utility, and substitution effect are the main influencing factors of low marginal WTP added value and embedding effect. When the quantity range changes, the utility of respondents tends to saturate and marginal utility rapidly decreases. Influenced by the aforementioned factors, the sum of the independent estimates of the respondents on the WTP for the improvement of agricultural green resources and environment of the photovoltaic industry in the four research areas is 3.04 times the average value of the overall estimates of the four areas. In order to obtain and maintain the local photovoltaic industry for agricultural production resources and environmental improvement, the average WTP of each respondent was 99.80 yuan per year.